The immunological footprint of CMV in HIV-1 patients stable on long-term ART. Issue 1 (December 2015) - Affandi, Jacquita; Montgomery, Jacinta; Brunt, Samantha; Nolan, David; Price, Patricia
Abstract Background Most HIV-infected persons are cytomegalovirus (CMV) seropositive and retain latent virus that can be reactivated by immune activation. Their T cell populations express markers reflecting a late stage of differentiation, but the contributions of HIV and CMV to this profile are unclear. We investigated the immunological "footprint" of CMV in HIV patients who had a history of extreme immunodeficiency but were now stable on antiretroviral therapy (ART). Results Twenty CMV seropositive HIV patients >50 years old with nadir CD4 T-cell counts <200 cells/μl were studied after >12 years on ART. 16 CMV seropositive and 9 CMV seronegative healthy controls were included. CMV antibody titres were higher in HIV patients than controls (P  < 0.001-0.003). Levels of soluble B-cell activating factor (sBAFF) were elevated in patients (P  = 0.002) and correlated with levels of CMV antibodies (P  = 0.03-0.002), with no clear relationship in controls. CD8 T-cell IFNγ responses to the IE1 peptide (VLE) remained elevated in HIV patients (P  = 0.005). The CD57+ CD45RA+ CD27− phenotype of CD8 T-cells correlated with age (r  = 0.60, P  = 0.006), antibodies against CMV IE1 protein (r  = 0.44, P  = 0.06) and CD4 T-cell IFNγ response to CMV lysate (r  = 0.45, P  = 0.05). Conclusions Humoral and T-cell responses to CMV remained elevated in HIV patients after >12 years on ART. Age and presence of CMV disease influenced CD8 T-cell phenotypes. Elevated levels of sBAFF may be a consequence of HIV disease and contribute to high titres of CMV antibody.